We Must Find a Stronger Theological Voice: A Copeland Dialectic to Address Racism, Bias, and Inequity in Technology - John P. Slattery (Journal of Moral Theology, 2022)
I divide the general field of technology ethics into two distinct parts, the ethics of applied technology and the ethics of technology and society. The former is the subject of volumes, whereas the latter is just beginning to emerge. This essay aims to bring the ethics of technology and society, with its emphasis on issues of bias, injustice, and equity, into conversation with contemporary political theology, and as such uncover new possibilities for theological reflection. To do this, I discuss how current theological utilizations of the common good are insufficient to provide a unique voice to the many biases and injustices within modern technological systems unless they are properly couched in an interruptive mystical-political framework, as defined here by M. Shawn Copeland, through her use of Bernard Lonergan and Johann-Baptist Metz, and marked by forgiveness, reconciliation, witness, memory, and lament.